Geochemistry of Li-bearing aplite-pegmatite veins from Cabeço Queimado and associated rocks (Segura, Central Portugal) - Antunes, I.M.H.R. (2011)
At Segura area, two-mica granite, muscovite granite, granitic aplite veins and Libearing granitic aplite-pegmatite veins from Cabeco Queimado intruded the Cambrian schist-metagraywacke complex. Aplite veins also intruded both granites. Variation diagrams of major and trace elements of the granitic rocks show fractionation trends for: a) two-mica granite and Li-bearing aplite-pegmatite veins; b) muscovite granite and aplite veins. Least square analysis for major elements and modelling of trace elements indicate that: a) the Li-bearing aplite-pegmatite veins were derived from the two-mica granite by factional crystallization of quartz, plagioclase, potash feldspar and biotite; b) the aplite veins were derived from muscovite granite by fractional crystallization of quartz, plagioclase, potash feldspar and ilmenite, which is supported by the similar δ18O values. The increase of δ18O values from two-mica granite to aplite-pegmatite veins suggests that fractional crystallization was accompanied by assimilation of metasedimentary material (AFC process). The pegmatite veins are REL-Li pegmatites and belong to the LCT family. The occurrence of amblygonite-montebrasite, lepidolite, cassiterite, ferrocolumbite, manganocolumbite and microlite suggest that Li-bearing granitic aplite-pegmatite veins are highly differentiated.